Equilibrium Policy Experiments and the Evaluation of Social Programs - Jeremy Lise; Shannon Seitz; Jeffrey Smith (Queen's University, Department of Economics, 2003)
This paper makes three contributions to the literature on program evaluation. First, we construct a model that is well-suited to conduct equilibrium policy experiments and we illustrate effectiveness of general equilibrium models as tools for the evaluation of social programs. Second, we demonstrate the usefulness of social experiments as tools to evaluate models. In this respect, our paper serves as the equilibrium analogue to LaLonde (1986) and others, where experiments are used as a benchmark against which to assess the performance of non-experimental estimators. Third, we apply our model to the study of the Canadian Self-Sufficiency Project (SSP), an experiment providing generous financial incentives to exit welfare and obtain stable employment. The model incorporates the main features of many unemployment insurance and welfare programs, including eligibility criteria and time-limited benefits, as well as the wage determination process. We first calibrate our model to data on the control group and simulate the experiment within the model. The model matches the welfare-to-work transition of the treatment group, providing support for our model in this context. We then undertake an equilibrium evaluation of the SSP. Our results highlight important feedback effects of the policy change, including displacement of unemployed individuals, lower wages for workers receiving supplement payments and higher wages for those not directly treated by the program. The results also highlight the incentives of individuals to delay exit from welfare in order to qualify for the program. Together, the feedback effects change the cost-benefit conclusions implied by the partial equilibrium experimental evaluation substantially.
Keywords: J2; I38; J6; 330; Program Evaluation; Self-Suficiency Project; Welfare; Social Experiments; Equilibrium Models; Aktivierende Arbeitsmarktpolitik; Arbeitsmarktpolitik; Wirkungsanalyse; Arbeitsmarkttheorie; Experiment; Kanada; Arbeitsmarktintegration; Gleichgewichtsmodell